A Practical Method to Improve Absolute Positioning Accuracy of Industrial Robot. (January 2020) - Shi, Guosong; Zhao, Shuying; Hu, Baolong
Abstract: Industrial robots had been wildly used in modern factory. While the high repeatability of industrial robots can address most of need of process, their low absolute positioning ability cannot reach the demands of some high precision tasks. An example is if the action of the robot relies on the real-time sampled data rather than the simulated data. The low absolute positioning ability of the robot will cause working performance far different away from expectation. For improving the absolute positioning accuracy as long as compile with the programs of automation integration projects, a practical general compensation method has been advanced. Our method also can be a compensation frame which can absorb new better model in the future. One application of this method in a project verifies the achievement of this method.